EVALUASI IMPLEMENTASI PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL DI SMA NEGERI 6 BALIKPAPAN - Wifa Rasuna Yasmin; Alya Puspita Zahra; Ambar Sri Pratiwi; Yasinta Monitasari; Ramadiani Ramadiani; Sudarman Sudarman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of digital technology has encouraged schools to integrate technology into the teaching and learning process to improve effectiveness, efficiency, and the overall quality of educational services. This study aims to describe the implementation of digital technology-based learning at SMA Negeri 6 Balikpapan, evaluate its success using the DeLone and McLean Information Systems Success Model, and identify the opportunities and challenges encountered during its implementation. This study employed a descriptive qualitative approach with a case study design. The participants consisted of the principal, the vice principal, the school operator, teachers, and students selected through purposive sampling. Data were collected through semi-structured interviews, non-participant observations, and documentation. The data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Data trustworthiness was ensured through triangulation, member checking, and an audit trail. The findings indicate that digital technology-based learning has been effectively implemented through various platforms, including Google Classroom, Google Forms, Canva, Quizizz, Kahoot, WhatsApp, YouTube, and Baamboozle. Based on the six dimensions of the DeLone and McLean Model, the system demonstrated satisfactory performance in terms of system quality, information quality, service quality, system use, user satisfaction, and net benefits. The implementation enhanced learning effectiveness, improved access to educational resources, and increased students' motivation and participation. However, several challenges remain, including unstable internet connectivity, uneven digital competencies among teachers, limited access to digital devices for some students, and the need for continuous infrastructure development and professional training. Keywords: DeLone and McLean Model, Digital learning implementation, Educational technology, Management information system.